2023
DOI: 10.1039/d2se01361d
|View full text |Cite
|
Sign up to set email alerts
|

Sub- and supercritical water conversion of organic-rich shale with low-maturity for oil and gas generation: using Chang 7 shale as an example

Abstract: Organic-rich shale resources are of large reserves and high hydrocarbon generation potential but difficult to be exploited due to its high solid kerogen content. Supercritical water conversion was proposed as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…This was because the increase in temperature promoted the free radical reaction for gas production. Our previous work reported that the optimal oil and gas yield of shale in SCW at the temperature range of 300–650 °C was respectively 0.35 g/gTOC at 380 °C and 0.59 g/gTOC at 650 °C . In comparison, the oil yield from kerogen was much lower than that from shale, but the gas yield was basically the same.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…This was because the increase in temperature promoted the free radical reaction for gas production. Our previous work reported that the optimal oil and gas yield of shale in SCW at the temperature range of 300–650 °C was respectively 0.35 g/gTOC at 380 °C and 0.59 g/gTOC at 650 °C . In comparison, the oil yield from kerogen was much lower than that from shale, but the gas yield was basically the same.…”
Section: Resultsmentioning
confidence: 93%
“…Our previous work reported that the optimal oil and gas yield of shale in SCW at the temperature range of 300−650 °C was respectively 0.35 g/gTOC at 380 °C and 0.59 g/gTOC at 650 °C. 40 In comparison, the oil yield from kerogen was much lower than that from shale, but the gas yield was basically the same. In this work, as the reaction temperature increased, SCW shifted from promoting the ionic reactions (around the critical point) to promoting free radical reactions.…”
Section: Hydrocarbon Generation Efficiencymentioning
confidence: 93%
See 3 more Smart Citations